Vape shop location and marketing in the context of the Food and Drug Administration regulation. (December 2018) - Berg, Carla J.
Abstract: Objectives: A range of electronic nicotine delivery systems (ENDSs; e.g. e-cigarettes, e-hookahs) have emerged in the US market, with rapid increases in use. While ENDSs may facilitate harm reduction in smokers, they may represent risks to health and addiction in the nicotine naïve. Vape shops account for a substantial proportion of ENDS sales/distribution. Study design: Brief summary of the relevant literature. Methods: This communication provides a brief summary of relevant literature derived from traditional tobacco retail and point-of-sale marketing and synthesizes issues regarding how the Food and Drug Administration regulation might impact the ENDS market, specifically the vape shop industry, a nuanced tobacco retail environment. Results: This literature indicates that tobacco retailers are disproportionately located near vulnerable populations (e.g. the socio-economically disadvantaged, racial/ethnic minorities, and young adults) and may use stronger promotional activities to target these populations. Research extending this literature to ENDSs and ENDS retailers, such as vape shops, is limited. Regulatory efforts, spatial access, and exposure to marketing and advertising are macrolevel factors that have a significant impact on the individual-level tobacco use. Conclusions: Future research should examine multilevel factors (e.g. policies, community context, and marketing) and extend this literature to the ENDS market, particularly vape shops, which is especially relevant during the rapidly changing regulatory environment. Highlights: The Food and Drug Administration regulation will impact the electronic nicotine delivery systems (ENDS) market. This is particularly relevant to vape shops, which exclusively focus on ENDS sales. Tobacco retailers have targeted vulnerable groups via the location and marketing. Research must examine if ENDS retailers, such as vape shops, target vulnerable groups. Multilevel influences and outcomes of regulatory change should be assessed.